2022
DOI: 10.3928/19382359-20220504-05
|View full text |Cite
|
Sign up to set email alerts
|

A Literature Review of Feeding Disorders in Children with Tracheostomies and Ventilators

Abstract: Feeding disorders and gastrostomy use are highly prevalent in children with invasive mechanical ventilation (IMV) due to both common risk factors (eg, prematurity, neurological disorders) and resultant experiential deprivation (eg, long hospitalizations, delayed feeding experiences). Feeding in children with IMV is complicated by the presence of a tracheostomy, lung vulnerability, and medical complexity. The potential comorbidity of swallowing difficulties (dysphagia) and atypical early feeding experiences can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 36 publications
0
11
0
Order By: Relevance
“…Another study looked at 5‐year outcomes of children with IMV and identified a high association between neurocognitive function and ventilator dependence, although cognitive assessment was determined by chart review and team consensus, without objective measures 17 . Mechanistically, it is thought that prolonged oral intubation and the presence of a tracheostomy may limit essential early speech and feeding opportunities, and increase likelihood of feeding problems and impaired oral motor skills underlying language expression 18–20 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study looked at 5‐year outcomes of children with IMV and identified a high association between neurocognitive function and ventilator dependence, although cognitive assessment was determined by chart review and team consensus, without objective measures 17 . Mechanistically, it is thought that prolonged oral intubation and the presence of a tracheostomy may limit essential early speech and feeding opportunities, and increase likelihood of feeding problems and impaired oral motor skills underlying language expression 18–20 …”
Section: Introductionmentioning
confidence: 99%
“…17 Mechanistically, it is thought that prolonged oral intubation and the presence of a tracheostomy may limit essential early speech and feeding opportunities, and increase likelihood of feeding problems and impaired oral motor skills underlying language expression. [18][19][20] As a whole, the developmental outcomes of children with IMV have been studied within larger premature cohorts, and have shown greater risk for developmental delays than other prematurely born infants. However, the extent of these delays, their distribution, trajectories, and protective or confounding influence across diverse populations are yet unknown.…”
mentioning
confidence: 99%
“…This finding may be secondary to multiple factors for which patients with tracheostomies are already at high risk, including feeding aversion and overall medical complexity. 23 A retrospective review of patients enrolled in an intensive tube weaning program found that patients with G-tubes (as opposed to NG tubes in their study) and those with a higher degree of medical complexity took significantly longer to wean from enteral feeding; nearly 40% of their G-tube cohort was unable to discontinue tube feeding at 3-year follow-up. 21 A previous study found that, among children with feeding disorders, those who had a tracheostomy had worse oral feeding skills and meal-time behaviors, had chronic malnutrition, and more often required enteral feedings.…”
Section: Discussionmentioning
confidence: 98%
“…In our study, patients with tracheostomy were found to require G‐tube feeds for a significantly longer period of time compared with those without tracheostomy. This finding may be secondary to multiple factors for which patients with tracheostomies are already at high risk, including feeding aversion and overall medical complexity 23 . A retrospective review of patients enrolled in an intensive tube weaning program found that patients with G‐tubes (as opposed to NG tubes in their study) and those with a higher degree of medical complexity took significantly longer to wean from enteral feeding; nearly 40% of their G‐tube cohort was unable to discontinue tube feeding at 3‐year follow‐up 21 .…”
Section: Discussionmentioning
confidence: 99%
“…29,30 The gastro-esophageal reflux (GER) disease, dysphagia, delayed gastric emptying and constipation are the most common GI problems of the children with tracheostomy on MV. [31][32][33] 2.1 | Ger disease impairement. [35][36][37][38] In the study of mechanical ventilated critically ill patients, the basal LES pressure was found to be low and a minimal increase in abdominal pressure due to suctioning, straining, coughing may cause frequent reflux episodes.…”
Section: Gi Problems In Children On Himvmentioning
confidence: 99%